Structure and bonding of proximity‐enforced main‐group dimers stabilized by a rigid naphthyridine diimine ligand. Issue 3 (1st September 2022) - Weiser, Jonas; Cui, Jingjing; Dewhurst, Rian D.; Braunschweig, Holger; Engels, Bernd; Fantuzzi, Felipe
Abstract: The development of ligands capable of effectively stabilizing highly reactive main‐group species has led to the experimental realization of a variety of systems with fascinating properties. In this work, we computationally investigate the electronic, structural, energetic, and bonding features of proximity‐enforced group 13–15 homodimers stabilized by a rigid expanded pincer ligand based on the 1, 8‐naphthyridine ( napy ) core. We show that the redox‐active naphthyridine diimine (NDI) ligand enables a wide variety of structural motifs and element‐element interaction modes, the latter ranging from isolated, element‐centered lone pairs (e.g., E = Si, Ge) to cases where through‐space π bonds (E = Pb), element‐element multiple bonds (E = P, As) and biradical ground states (E = N) are observed. Our results hint at the feasibility of NDI‐E2 species as viable synthetic targets, highlighting the versatility and potential applications of napy ‐based ligands in main‐group chemistry. Abstract : Geometries, electronic structures, energetics, and bonding situations of 15 naphthyridine diimine (NDI)‐stabilized main‐group dimers E2 from groups 13, 14 and 15 are investigated utilizing distinct computational approaches. The E–E interaction modes vary from element‐centered lone pairs (e.g., E = Si, Ge) to through‐space π bond (E = Pb), E–E multiple bonds (E = P, As) and triplet ground state (E = N). NDI‐E2 systems are predicted as potential targets for further experimental investigation.